2015
DOI: 10.1055/s-0034-1397338
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Hearing Handicap and the Recognition Threshold of Sentences of a Patient with Unilateral Auditory Neuropathy Spectrum Disorder with Use of a Hearing Aid

Abstract: Introduction Treatment for auditory neuropathy spectrum disorder (ANSD) is not yet well established, including the use of hearing aids (HAs). Not all patients diagnosed with ASND have access to HAs, and in some cases HAs are even contraindicated. Objective To monitor the hearing handicap and the recognition threshold of sentences in silence and in noise in a patient with ASND using an HA. Resumed Report A 47-year-old woman reported moderate sensorineural hearing loss in the right ear and high-frequency loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The early diagnosis and management of ANSD could lead to a reduction in handicap. Lima and Mantello [22] reported significant reduction in handicap score with appropriate hearing aid fitting. However, hearing aids are less beneficial in the majority of individuals with ANSD [1,4,27,[35][36][37] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The early diagnosis and management of ANSD could lead to a reduction in handicap. Lima and Mantello [22] reported significant reduction in handicap score with appropriate hearing aid fitting. However, hearing aids are less beneficial in the majority of individuals with ANSD [1,4,27,[35][36][37] .…”
Section: Discussionmentioning
confidence: 98%
“…ANSDis a debilitating disorder affecting communication ability. The loss of communication skills leads to poor quality of life in adults with ANSD [21,22] . Prabhu [14] reported that individuals with ANSD experience depression and anxiety because of their communication problems.…”
Section: Introductionmentioning
confidence: 99%
“…Lima, et al [ 19 ] monitored speech recognition threshold (SRT) of a client with late onset ANSD in quiet and noisy environments. The client had moderate hearing loss in the right ear and normal threshold in low frequencies with a slight high frequency sloping in the left ear.…”
Section: Introductionmentioning
confidence: 99%